Effect of formalin fixation on biexponential modeling of diffusion decay in prostate tissue. Issue 4 (15th November 2012) - Bourne, Roger; Bongers, Andre; Charles, Ned; Power, Carl; Sved, Paul; Watson, Geoffrey
<x xml:space="preserve">Abstract</x> Purpose To evaluate the effect of formalin fixation on biexponential modeling of diffusion decay in prostate tissue. Methods Three whole prostate specimens were imaged unfixed immediately postsurgery, and again after formalin fixation. Diffusion‐weighted imaging was performed over an extended range of b‐values and a biexponential model fitted to the signal decay curves. Results Tissue fixation resulted in a 35%, 20%, and 20% reduction in mean apparent diffusion coefficient of the higher diffusivity fit component for the three organs, respectively, and a 64%, 57%, and 45% reduction in mean apparent diffusion coefficient of the lower diffusivity component. The mean signal fraction of the higher diffusivity component was increased by 23%, 5%, and 1%, respectively. The effect of fixation did not appear to vary according to tissue type or glandular zone. Conclusion Formalin fixed tissue appears to provide a stable model for detailed investigation of the microscopic biophysical basis of diffusion phenomena observed in vivo. Diffusivity changes that result from fixation may provide information about the microscopic environments of the biexponential components. Magn Reson Med, 70:1160–1166, 2013. © 2012 Wiley Periodicals, Inc.